Coming out as an autistic researcher: academic writing and its breakdowns - Boven, Frederik (Frontiers in Psychiatry, 2026)
This descriptive article offers an inside perspective of the experience of writing a publishable paper by an autistic early-career researcher. From an external perspective, this experience might be described as involving hyperfocus, indecision about framing, and conflicting norms of academic writing. The article develops an inside perspective on such experiences. The author adopts a philosophical approach, using phenomenological reflection on breakdowns as a method to explicate what is implicitly given in experience. Reflection on three types of research breakdown in academic writing results in an inside description of the complexities of this particular experience by someone who is both autistic and an academic researcher.